Four Regulatory Principles to Promote Diverse Electrification - Reiche, Kilian; Tenenbaum, Bernard; Torres, Clemencia (World Bank, Washington, DC, 2014)
This note is a summary of a study to be published by ESMAP and the Energy and Mining Sector Board in 2006. The study proposes four principles for regulatory systems that will help, rather than hinder, electrification. The principles and the accompanying real world examples show how successful electrification often requires that the traditional functions of regulation be performed in non-traditional ways.